(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Heterocyclic compounds display distinct applications in the agricultural field due to their diverse chemical properties. Heterocyclic compounds are popular in agricultural chemistry and play a key role in the agrochemical industry. This article will focus solely on the application of synthetic compounds in an agricultural field. A variety of pesticides have been developed as insecticides, fungicides, plant growth regulators, nematicides, rodenticides, Larvicides, bactericides and herbicides. The article’s main goal is to provide information about heterocyclic compounds, which make up the largest class of agrochemical compounds. These are essential, having a broad range of industrial, agricultural, and synthetic uses.